Comparative study of functional outcome between plantar fascia stretching and achilles tendon stretching exercises in choronic plantar fasciitis - Shrestha, S; Rai, S; Limbu, H; Bajracharya, S (Nepal Journal of Medical Sciences, 2015)
Background: Plantar fasciitis is a self limiting disease, with only 10% of patient developing chronic condition even after ten months. We hypothesized that patient with chronic plantar fasciitis who are treated with standard plantar fascia stretching program can have a better functional outcome than those treated with Achilles tendon-stretching exercise. Method: Forty patients who had chronic plantar fasciitis for duration of at least ten months were randomized into one of two groups. Group A received plantar stretching exercise and Group B had Achilles tendon stretching program. All patients completed the pain subscale of Foot Function Index and a subject relevant outcome survey that incorporated generic and condition-specific outcome measures related to pain, function and satisfaction with treatment outcome. Result: The pain subscale scores of the Foot Function Index showed significantly better results at eight weeks for the patients managed with plantar fascia stretching program respect to item 1 (worst pain; p = 0.004) and item 2 (first steps in the morning; p =0.001). Similarly at ten months follow up, pain subscale score comparison was statistically significant for item 1 (p = 0.018) and item 2 (p =0.003). Conclusions: A treatment method of non-weight-bearing stretching exercises specific to plantar fascia is superior to the conventional method of weight-bearing Achilles tendon-stretching exercises for treating patients with chronic plantar fasciitis. Nepal Journal of Medical Sciences Vol.3(2) 2014: 84-88